Diversity of the Insect Visitors on Calluna vulgaris (Ericaceae) in Southern France Heathlands. Issue 1 (21st September 2015) - Descamps, Charlotte; Moquet, Laura; Migon, Marc; Jacquemart, Anne-Laure
Abstract : As part of an ongoing research project on the pollination networks in European heathlands, the objective of this study was to assess the insect visitor guild on Calluna vulgaris (L.) Hull (Ericaceae). We focused the study on a region renowned for its largely well-preserved heathlands, the Cévennes National Park, Southern France. In 2013, flower visitors were observed over 3 d per site, in four heathland sites at mont Lozère. Honeybees ( Apis mellifera L.) were the main visitors (62–88% of total visitors). Besides honeybees, a high diversity of visitors was detected with 57 different species identified (42 Diptera and 15 Hymenoptera). Hoverflies (Syrphidae, Diptera) visitors were abundant and diverse, especially individuals belonging to the genera Eristalis and Episyrphus . The reported diversity of visitors was probably due to the preservation of large heathland areas at mont Lozère and to the generalist pollination system of C. vulgaris . RESUME . Cette étude fait partie d'un projet de recherche en cours sur les réseaux de pollinisation dans les landes européennes. Son objectif est d'évaluer la guilde des insectes visiteurs de Calluna vulgaris (L.) Hull (Ericaceae) . Cette étude se déroule dans une région réputée pour ses landes globalement bien préservées: le Parc natinal des Cévennes, situé dans le sud de la France. En 2013, les insectes visiteurs ont été observés durant trois jours par site, dans quatre sites au mont Lozère. Les abeilles domestiques ( A. mellifera L.) sont les visiteurs principaux (62–88% du nombre total de visiteurs). Outre les abeilles domestiques, une diversité importante de visiteurs est constatée: 57 espèces ont été identifiées (42 appartenant à l'ordre des Diptères et 15 à l'ordre des Hyménoptères). Les syrphes (Syrphidae, Diptera) sont abondants et diversifiés, en particulier les genres Eristalis et Episyrphus . La diversité de visiteurs observée peut certainement s'expliquer par la préservation de grandes étendues de landes au mont Lozère et par le caractère généraliste de la pollinisation de la callune.